PERANAN HUKUM DALAM TECHNICAL ASISSTANCE CONTRACT DAN TRANSFER OF TECHNOLOGY PADA PERUSAHAAN PERTAMBANGAN MINYAK DAN GAS BUMI DITINJAU DARI UNDANG-UNDANG NO. 25 TAHUN 2007 - , Yufrida, SH., SE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Oil and Gas Mining company (Pertamina) was established by Law No.. 8 of 1971 on Pertamina, which stated that the State provide mining rights in full and absolute to a state company established by Law. Pertamina as the authorized executive of state oil mining rights, under Article 12 of Law No. 8 of 1971 to cooperate with the contractors in the form of \"Production Sharing Contract\", in addition to the mining area managed also conduct its own operations as well as did the contract with Production Sharing Contract Models, one of which in the form of Technical Assistance Contract (TAC). By the issuance the Law No. 22 of 2001 on Oil and Gas with Government Regulation No. . 42 of 2002 on the Executive Agency for Upstream Oil and Gas Activities as well as Government Regulation No. 35 of 2004 on Upstream Oil and Gas Activities, the company's goals are to develop and implement control of oil and gas in the broadest sense for the prosperity of the people and the state as well as to create national resilience. In real conditions between Pertamina and private companies as a partner, cooperative relationships set forth in the form of contracts, one of which Technical Assistance Contract (TAC), which aims to increase production from old wells with advanced technology. Technical Assistance Contract (TAC) Formulation has been prepared by Pertamina and is expected to also perform Transfer of Technology in accordance with the provisions of Law No. 25 of 2007 on Investment, which is expected to benefit Indonesia in this case Pertamina, because in addition to the provisions of the arbitrase then the law selected and forum chosen is Indonesian court.